Knowledge of personal hygiene and waterborne diseases and practice of personal hygiene among students of Central Agricultural University, Manipur, India - Kumar, K. Sathish; Akoijam, Brogen Singh (International Journal Of Community Medicine And Public Health, 2017)
Background:Adverse health outcomes are associated with ingestion of unsafe water and poor personal hygiene. Approximately 3.1% of deaths (1.7 million) and 3.7% of DALYs (54.2 million) worldwide are attributable to unsafe water, poor sanitation and poor personal hygiene. Methods:This was a cross sectional study conducted among students of Central Agricultural University, Imphal during the period of 18/3/2014 to 4/4/2014. Data was collected by a self-administered questionnaire. Data entry and analysis was done using IBM SPSS version-21. Results:About 85.5% of the respondents knew correctly the meaning of personal hygiene. Nearly half of the respondents said that diarrhea can be prevented by maintaining good personal hygiene but only 5.8% of the respondents said that skin diseases can be prevented. Out of the 7 steps of proper hand washing, only 2 steps were known to the respondents. About 56.5% of the respondents knew the meaning of water borne diseases. Diarrhea was the most common water borne disease known to majority (63.5%) of the respondents. Only 34.4% of the respondents had the habit of washing hands after work and only 9.4% of the respondents washed their hands after playing. Conclusions:It is recommended to conduct further studies to assess their personal hygiene practices in detail and demonstrate them proper hand washing and hygiene practices.